Arthur Davison Ficke papers concerning Donald Evans, - Lowell, Amy, 1874-1925; Evans, Donald, 1884-1921.
Correspondence between Donald Evans and Arthur Ficke; typescripts of several newspaper articles, with poems, by Evans; and typescript letters from Amy Lowell, among other correspondents, to Evans.